Evidence-Based School Counseling: Models for Integrated Practice and School Counselor Education. (January 2018) - Zyromski, Brett; Dimmitt, Carey; Mariani, Melissa; Griffith, Catherine
Although school counselors and school counselor educators have an ethical responsibility to use and to teach evidence-based practices (EBPs), recent research has illustrated a lack of EBP in counselor education scholarship. In school counselor education programs, training related to EBP may be absent due to a lack of understanding or instructor training. This article provides a model using three pedagogical approaches for integrating EBP into school counselor education programs. We review the three approaches—stand-alone courses, full program integration, and program–school–community integration—in depth and use a case study to illustrate the application of the three approaches. Implications for school counseling practice and research conclude the article.